(untitled) (Research, Society and Development, 2025)
Glioblastoma multiforme (GBM) is the most common and aggressive primary malignant brain tumor in adults, characterized by a high recurrence rate and low median survival, even with multimodal treatment. The current therapeutic approach involves maximal safe surgical resection, followed by radiotherapy and chemotherapy with temozolomide. In recent years, technological and scientific advances have expanded therapeutic possibilities, including the use of neuronavigation, intraoperative fluorescence with 5-aminolevulinic acid (5-ALA) and awake surgery, allowing greater tumor resection with functional preservation. In addition, innovative therapies are emerging, such as immunotherapy, molecular-targeted therapies, use of alternating electric fields (Optune) and drug delivery strategies with nanotechnology. This review article aims to present the main therapeutic advances in the management of GBM, highlighting the fundamental role of surgery in the context of integrated treatment, and discuss future perspectives in tackling this tumor with highly invasive behavior and reserved prognosis.